Upaya Peningkatan Kemampuan Keluarga Dalam Pengelolaan Beban Perawatan Melalui Psikoedukasi Keluarga Dirumah Sakit Umum - Emilia Puspitasari S; Achir Yani S Hamid; Yossie Susanti E P (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2015)
The Health status alteration of the familly members is one of the stessor which effected to the family. Disbility of the family to solve the stressor, caused familly burden. Some efforts needed to support the familly to solves the problem. The final scientific work was to obtain an overview of efforts to increase the family's ability to manage the burden of care in hospitals. There are 24 families that have been analyzed by the Roy's Adaptation Model. The result is indicated the decreation of the family burden, and showed the increation of the family ability to take care the family member while showed the increation of family burden management. This result recommended the application of the family nursing care management in hospitasl to increased the ability of family member nursing either to increased the ability of family burden management.